COMT Val158Met Polymorphism, Cardiometabolic Risk, and Nadir CD4 Synergistically Increase Risk of Neurocognitive Impairment in Men Living With HIV. (15th August 2019) - Saloner, Rowan; Marquine, Maria J.; Sundermann, Erin E.; Hong, Suzi; McCutchan, John Allen; Ellis, Ronald J.; Heaton, Robert K.; Grant, Igor; Cherner, Mariana
Abstract : Objective: The Val allele of the Val158Met single-nucleotide polymorphism of the catechol-o-methyltransferase gene ( COMT ) results in faster metabolism and reduced bioavailability of dopamine (DA). Among persons living with HIV, Val carriers display neurocognitive deficits relative to Met carriers, presumably due to exacerbation of HIV-related depletion of DA. COMT may also impact neurocognition by modulating cardiometabolic function, which is often dysregulated among persons living with HIV. We examined the interaction of COMT, cardiometabolic risk, and nadir CD4 on neurocognitive impairment (NCI) among HIV+ men. Methods: Three hundred twenty-nine HIV+ men underwent COMT genotyping and neurocognitive and neuromedical assessments. Cohort-standardized z scores for body mass index, systolic blood pressure, glucose, triglycerides, and high-density lipoprotein cholesterol were averaged to derive a cardiometabolic risk score (CMRS). NCI was defined as demographically adjusted global deficit score of ≥0.5. Logistic regression modeled NCI as a function of COMT, CMRS, and their interaction, covarying for estimated premorbid function, race/ethnicity, and HIV-specific characteristics. Follow-up analysis included the 3-way interaction of COMT, CMRS, and nadir CD4. Results: Genotypes were 81 (24.6%) Met/Met, 147 (44.7%) Val/Met, and 101 (30.7%) Val/Val. COMT interacted with CMRS ( P = 0.02) such that higher CMRS increased risk of NCI among Val/Val [odds ratio (OR) = 2.13, P < 0.01], but not Val/Met (OR = 0.93, P > 0.05) or Met/Met (OR = 0.92, P > 0.05) carriers. Among Val/Val, nadir CD4 moderated the effect of CMRS ( P < 0.01) such that higher CMRS increased likelihood of NCI only when nadir CD4 <180. Discussion: Results suggest a tripartite model by which genetically driven low DA reserve, cardiometabolic dysfunction, and historical immunosuppression synergistically enhance risk of NCI among HIV+ men, possibly due to neuroinflammation and oxidative stress.